The C-Type Lectin Receptor DC-SIGN Has an Anti-Inflammatory Role in Human M(IL-4) Macrophages in Response to Mycobacterium tuberculosis - Lugo-Villarino, Geanncarlo; Troegeler, Anthony; Balboa, Luciana; Lastrucci, Claire; Duval, Carine; Mercier, Ingrid; Bénard, Alan; Capilla, Florence; Al Saati, Talal; Poincloux, Renaud; Kondova, Ivanela; Verreck, Frank A. W.; et al. (Frontiers in Immunology, 2018)
DC-SIGN (CD209/CLEC4L) is a C-type lectin receptor (CLR) that serves as a reliable cell-surface marker of interleukin 4 (IL-4)-activated human macrophages (M(IL-4)), which historically represent the most studied subset within the M2 spectrum of macrophage activation. Although DC-SIGN plays important roles in Mycobacterium tuberculosis (Mtb) interactions with dendritic cells, its contribution to the Mtb-macrophage interaction remains poorly understood. Since high levels of IL-4 are correlated with Tuberculosis (TB) susceptibility and progression, we investigated the role of DC-SIGN in M(IL-4) macrophages in the TB context. First, we demonstrate that DC-SIGN expression is present both in CD68+ macrophages found in tuberculous pulmonary lesions of non-human primates (NHP), and in the CD14+ cell population isolated from pleural effusions obtained from TB patients (TB-PE). Likewise, we show that DC-SIGN expression is accentuated in M(IL-4) macrophages derived from peripheral blood CD14+ monocytes isolated from TB patients, or in macrophages stimulated with acellular TB-PE, arguing for the pertinence of DC-SIGN-expressing macrophages in TB. Second, using a siRNA-mediated gene silencing approach, we performed a transcriptomic analysis of DC-SIGN-depleted M(IL-4) macrophages and revealed the up-regulation of pro-inflammatory signals in response to challenge with Mtb, as compared to control cells. This pro-inflammatory gene signature was confirmed by RT-qPCR, cytokine/chemokine-based protein array and ELISA analyses. We also found that inactivation of DC-SIGN renders M(IL-4) macrophages less permissive to Mtb intracellular growth compared to control cells, despite the equal level of bacteria uptake. Last, at the molecular level, we show that DC-SIGN antagonizes the pro-inflammatory response and control of Mtb intracellular growth mediated by another CLR, Dectin-1 (CLEC7A). Collectively, this study highlights a dual role for DC-SIGN as, on the one hand, being a host factor granting advantage for Mtb to parasitize macrophages and, on the other hand, representing a molecular switch to turn off the pro-inflammatory response in these cells to prevent potential immunopathology associated to TB.